2015
DOI: 10.1016/j.immuni.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Bcl11b Controls Identity and Function of Mature Type 2 Innate Lymphoid Cells

Abstract: Summary Type-2 innate lymphoid cells (ILC2s) promote anti-helminth responses and contribute to allergies. Here we report that Bcl11b, previously considered a T-cell lineage identity transcription factor, acts directly upstream of the key ILC2 transcription factor Gfi1 to maintain its expression in mature ILC2s. Consequently, Bcl11b−/− ILC2s downregulated Gata3 and downstream genes, including Il1rl1, encoding IL-33 receptor, and upregulated Rorc and type-3 ILC (ILC3) genes. Additionally, independent of Gfi1, Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
152
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(164 citation statements)
references
References 50 publications
12
152
0
Order By: Relevance
“…Also, Id2 is very easily up-regulated with any reduction of Bcl11b level, suggesting that Bcl11b may only weakly repress this gene. Recently, too, the type 2 ILC lineage has been shown to depend on Bcl11b as well as on Id2 (11,32,33), proving that the two can be coexpressed. Most genes de-repressed in Bcl11b KOs (Datasets S1 and S2) are more typical of NK, ILC1, and ILC3 cells than of ILC2 cells (54,56), suggesting that low levels of Bcl11b may block these alternatives while still allowing Id2 expression in ILC2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Id2 is very easily up-regulated with any reduction of Bcl11b level, suggesting that Bcl11b may only weakly repress this gene. Recently, too, the type 2 ILC lineage has been shown to depend on Bcl11b as well as on Id2 (11,32,33), proving that the two can be coexpressed. Most genes de-repressed in Bcl11b KOs (Datasets S1 and S2) are more typical of NK, ILC1, and ILC3 cells than of ILC2 cells (54,56), suggesting that low levels of Bcl11b may block these alternatives while still allowing Id2 expression in ILC2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…2A) (1), but the exact role of Bcl11b in this process depends on the unique regulatory context, which is not duplicated in any of the later T-cell contexts where Bcl11b works (reviewed in ref. 10) nor in type 2 ILC, where it also has a role (11,32,33). Until commitment (Fig.…”
Section: T-cell Specification Grn Transitions At Commitment: a Distinctmentioning
confidence: 98%
“…Therefore, consistently with their expression patterns, Runx1 and Runx3 appear to cooperate in regulating T-cell development at multiple stages; Runx1 is more important during early development of thymic precursors (DN and DP) while Runx3 becomes a CD8-lineage commitment factor (CD8 SP) [44]. Bcl11b is expressed mainly in T cells in mice, but recent studies showed that Bcl11b is also expressed in innate lymphoid cells [45]. During thymocyte differentiation, expression of Bcl11b is rapidly induced from DN2a stage, and it plays an important role in T-cell specification by driving DN2a cells into DN2b stage partly by upregulating some essential components of pre-TCR such as Zap70 and Ptcr-α but not .…”
mentioning
confidence: 85%
“…Bcl11b is expressed mainly in T cells in mice, but recent studies showed that Bcl11b is also expressed in innate lymphoid cells [45]. During thymocyte differentiation, expression of Bcl11b is rapidly induced from DN2a stage, and it plays an important role in T-cell specification by driving DN2a cells into DN2b stage partly by upregulating some essential components of pre-TCR such as Zap70 and Ptcr-α but not CD3 and RAG-1 [46].…”
Section: Role Of Transcription Factors In Early T-cell Developmentmentioning
confidence: 99%
“…Additionally, Bcl11b restricts expression of Th2 lineage genes in Th17 cells in experimental autoimmune encephalomyelitis (EAE) (33). Bcl11b was recently found to sustain innate lymphoid type 2 cell (ILC2) program (34,35,36) and to suppress ILC3 program in ILC2s…”
mentioning
confidence: 99%